UPAYA MENINGKATKAN KETERAMPILAN MENULIS SINOPSIS NOVEL “AYAH MENGAPA AKU BERBEDA” KARYA AGNES DAVONAR DENGAN MODEL PEMBELAJARAN STAD - Arta Roneli Siregar (PANTAK: Jurnal Penelitian Tindakan Kelas, 2024)
This study aims to obtain objective data on Efforts to Improve Writing Skills Synopsis of Novel "Ayah Mengapa Aku Perbedaan" by Agnes Davonar by Using Stad Learning Model on Students of Grade VII MTs Negeri 2 Padangsidimpuan in Academic Year 2013-2014. This study uses descriptive method with the population of the study is all students of grade VII MTs Negeri 2 Padangsidimpuan in Academic Year 2013-2014 consisting of four classes totaling 140 students. The sample of this study amounted to 35 students. The research method used is Classroom Action Research (CAR). Classroom Action Research (CAR) also seeks to improve learning conditions and solve various problems that arise in the classroom. The data analysis technique used is descriptive qualitative. The research instrument is to create a novel synopsis, the author sets the highest value of 100 and the lowest 0 and the results of the study indicate that students of class VII MTs Negeri 2 Padangsidimpuan in the 2013-2014 Academic Year have "Good" abilities. This result can be seen from the average value obtained, the rest shows 7 with the assessment submitted or stated to have qualifications based on a value range of 75-84%. These results indicate the existence of novel synopsis writing skills.